The motivation of the swimmers to do sports - Raslanas, A.; Stakyte, S. (8th International Sports Science Conference, Vilnius, 25-26 February 2005, 2005)
The aim of this work was to determine the main motivations of young and skilful swimmers. The following tasks were set: to determine the motivation of young and skilful swimmers and the main sports motivations of young women and men.